2021
DOI: 10.1038/s43246-021-00173-8
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive bidirectional extracellular electron transfer during accelerated microbiologically influenced corrosion of stainless steel

Abstract: Microbiologically influenced corrosion of metals is prevalent in both natural and industrial environments, causing enormous structural damage and economic loss. Exactly how microbes influence corrosion remains controversial. Here, we show that the pitting corrosion of stainless steel is accelerated in the presence of Shewanella oneidensis MR-1 biofilm by extracellular electron transfer between the bacterial cells and the steel electrode, mediated by a riboflavin electron shuttle. From pitting measurements, X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…Shewanella oneidensis MR-1 is an attractive model microorganism for the study of corrosion mechanisms because: it is genetically tractable; it grows aerobically and anaerobically; it grows with H 2 as the electron donor; it can oxidize reduced flavins to support respiration; and it is capable of direct electron exchange with minerals and electrodes (Fredrickson et al, 2008;Hernandez-Santana et al, 2022;Jiang et al, 2020;Ross et al, 2011;Rowe et al, 2018;Shi et al, 2016). Anaerobic corrosion via H 2 or flavins as electron shuttles as well as direct electron uptake from Fe 0 have all been proposed as potential mechanisms for corrosion by S. oneidensis and related species (Herrera and Videla, 2009;Jiang et al, 2020;Jin et al, 2019;Kalnaowakul et al, 2020;Li et al, 2021aLi et al, , 2021bLutterbach et al, 2009;Miller et al, 2018;Philips et al, 2018;Schütz et al, 2015;Shi et al, 2006;Turick et al, 2002;Windt et al, 2003;Wurzler et al, 2020). However, none of the suggested mechanisms were rigorously evaluated with construction of the appropriate mutant strains or other strategies to rule out alternative mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Shewanella oneidensis MR-1 is an attractive model microorganism for the study of corrosion mechanisms because: it is genetically tractable; it grows aerobically and anaerobically; it grows with H 2 as the electron donor; it can oxidize reduced flavins to support respiration; and it is capable of direct electron exchange with minerals and electrodes (Fredrickson et al, 2008;Hernandez-Santana et al, 2022;Jiang et al, 2020;Ross et al, 2011;Rowe et al, 2018;Shi et al, 2016). Anaerobic corrosion via H 2 or flavins as electron shuttles as well as direct electron uptake from Fe 0 have all been proposed as potential mechanisms for corrosion by S. oneidensis and related species (Herrera and Videla, 2009;Jiang et al, 2020;Jin et al, 2019;Kalnaowakul et al, 2020;Li et al, 2021aLi et al, , 2021bLutterbach et al, 2009;Miller et al, 2018;Philips et al, 2018;Schütz et al, 2015;Shi et al, 2006;Turick et al, 2002;Windt et al, 2003;Wurzler et al, 2020). However, none of the suggested mechanisms were rigorously evaluated with construction of the appropriate mutant strains or other strategies to rule out alternative mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…oneidensis MR-1 biofilms on stainless steel. Li et al utilized riboflavin, an endogenous redox mediator produced by Shewanella, and polarized the ultramicroelectrode tip of SECM to either riboflavin reducing (−0.6 V vs Ag|AgCl) or oxidizing (−0.2 V vs Ag|AgCl) potentials, while biofilms of the bacterial cells were grown on stainless steel electrodes with or without passive layers . The study provided in situ evidence of the EET process taking place during the corrosion process, and revealed that the bacterial cells can perform bidirectional extracellular electron transfer using the diffusible mediator depending on the state of the steel surface (active or passive).…”
Section: Methods To Study Enzymatic and Microbial Electrodesmentioning
confidence: 99%
“…In general, dissimilatory metal-reducing bacteria (DMRB) oxidise organic matter, including organic contaminants and hydrogen gas (H 2 ) in anoxic environments, and then transmit the released electrons to solid-phase minerals containing oxidised metal ions, such as manganese (Mn(IV)) and ferric iron (Fe(III)) for anaerobic respiration [38]. These microorganisms are commonly involved in the degradation/corrosion of organic matter [130] and metals [131,132], e.g., Pb, Cd, and As, in surface and sub-surface environments such as sediments of rivers, soils, lakes, and oceans. Additionally, the bacteria involved have the potential to dramatically alter the geochemistry of the surrounding Fe mineral-containing As in groundwater and sediments, resulting in As contamination of drinking water sources, diseases, poisoning, and human health disruption [39,133,134].…”
Section: Effect Of Dissimilatory Iron-reducing Bacteria's Transformat...mentioning
confidence: 99%